MENINGKATKAN KETERAMPILAN MEMBACA MENGGUNAKAN MEDIA BUKU CERITA BERGAMBAR KELAS III SDN 1 TAMBAH SUBUR - Jujun Apriyana; Binti Khoiriyah; Nurkaif (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The factor causing the low reading skills of third grade students is due to the use of less interesting learning media so that students quickly feel bored and unmotivated to read. This study aims to improve students' reading skills through the use of picture storybooks. The study used the Classroom Action Research (CAR) method which was carried out in two cycles with 23 students as subjects. Assessments were carried out on aspects of reading fluency, pronunciation, and intonation. The results showed an increase in reading skills from Cycle I to Cycle II. In the aspect of reading fluency, the Very Good category increased from 43.48% to 56.53%, in the Good category increased from 13.04% to 26.09%, while in the Fair category decreased from 43.48% to 17.38%. In the pronunciation aspect, the Very Good category increased from 8.70% to 13.04%, in the Good category increased from 39.13% to 65.22%, while the Fair category decreased from 52.17% to 21.74%. In terms of intonation, there was no improvement in the Very Good category, but in the Goodcategory it increased from 30.43% to 65.22%, and in the Fair category it decreased from 56.53% to 21.74%. There were no students in the Poor category in either cycle. Based on these results, it can be concluded that the use of picture storybooks is effective in improving the reading skills of third-grade students.